2022
DOI: 10.3390/pathogens11101080
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus Detection in the Central Nervous System of HIV-Infected Patients

Abstract: Simply detecting Epstein–Barr virus deoxyribonucleic acid (EBV-DNA) is insufficient to diagnose EBV-associated diseases. The current literature around EBV-DNA detection from cerebrospinal fluid (CSF) in human immunodeficiency virus (HIV)-positive non-lymphoma patients was systematically reviewed and a meta-analysis reporting the estimated pooled prevalence in this population when PCR methods are employed, targeting different sequence segments within the EBV genome, was conducted. Using a combination of three k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Research has demonstrated that infection of the CNS with EBV in people living with HIV is associated with reactivated EBV [29]. Although the presence of EBV in the CNS remains a concern, co‐infections in EBV seem to play an important role in the success of its reactivation [30]. Early initiation of combination ART to help restore impaired immune surveillance and T‐cells is still an essential factor in the control of EBV for people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that infection of the CNS with EBV in people living with HIV is associated with reactivated EBV [29]. Although the presence of EBV in the CNS remains a concern, co‐infections in EBV seem to play an important role in the success of its reactivation [30]. Early initiation of combination ART to help restore impaired immune surveillance and T‐cells is still an essential factor in the control of EBV for people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis revealed that EBV is detectable in the cerebrospinal fluid (CSF) of approximately 20% of HIV-positive patients without lymphoma. 31 Similarly to JCV, in situations of cellular immunodeficiency, EBV can shift into an intensified replication state. 32 In addition to possibly causing symptomatic infections such as encephalitis, meningitis, and myelitis, EBV is also suspected to have a key role in the development of lymphoproliferative diseases.…”
Section: Introductionmentioning
confidence: 99%